ASSOCIATION BETWEEN RETINAL HEMORRHAGIC PATTERNS AND PERFUSION STATUS IN EYES WITH ACUTE CENTRAL RETINAL VEIN OCCLUSION. Issue 3 (March 2017) - Muraoka, Yuki; Uji, Akihito; Tsujikawa, Akitaka; Murakami, Tomoaki; Ooto, Sotaro; Suzuma, Kiyoshi; Takahashi, Ayako; Iida, Yuto; Miwa, Yuko; Hata, Masayuki; Yoshimura, Nagahisa
Abstract : Purpose: To evaluate peripheral retinal hemorrhagic patterns in eyes with acute central retinal vein occlusion, and to explore their clinical relevance in differentiating for the retinal perfusion status, through a prospective, and cross-sectional study. Methods: Fifty eyes with acute central retinal vein occlusion were included. Retinal hemorrhagic patterns at the equator and retinal perfusion status were evaluated by ultra-wide field fundus photography and fluorescein angiography. Results: Retinal perfusion was categorized as nonischemic in 29 eyes, ischemic in 18 eyes, and undeterminable in 3 eyes. None of the examined eyes had flame-shaped retinal hemorrhages in the periphery. All hemorrhages were rounded-dot or blot and were variable in size. Particle analysis was performed to quantify hemorrhage size, and showed higher values in eyes having larger blot hemorrhages, and lower values in eyes having dot or smaller blot hemorrhages. Mean size of maximum peripheral dot or blot hemorrhage was larger in eyes classified as ischemic (10, 763.0 ± 5, 946.3 pixels) than as nonischemic (2, 839.9 ± 1, 153.6 pixels, P < 0.001). The authors calculated area under the curve to investigate the ability of continuous variables to discriminate retinal perfusion status, which was 0.963 ( P < 0.001) for mean size of maximum peripheral blot hemorrhages. Conclusion: The authors objectively evaluated retinal hemorrhagic patterns at the equator in eyes with acute central retinal vein occlusion using particle analysis. The resulting hemorrhage size measurement was considered to be often useful in determining retinal perfusion status. Because they can be noninvasively evaluated with readily available equipment, peripheral hemorrhagic patterns might be good clinical markers of retinal perfusion. Abstract : The authors quantitatively evaluated retinal hemorrhagic patterns using ultra-wide field color fundus photography of the periphery of eyes with acute central retinal vein occlusion. Particle analysis was successfully used to quantify retinal hemorrhage size, and was useful in differentiation between nonischemic and ischemic central retinal vein occlusion. Because ultra-wide field photography is noninvasive, widely available, and easy to evaluate, peripheral hemorrhagic patterns might be effective clinical markers for retinal perfusion status.